The influence of corporate governance and organizational capacity on the performance of Malaysian listed companies - Mustapa, Ifa Rizad; Mohd. Ghazali, Nazli Anum; Mohamad, Muslim Har Sani (MCSER-CEMAS-Sapienza University of Rome, 2015)

(untitled)
This study assesses the association between corporate governance and performance of companies listed on Bursa Malaysia.Although there is no clear evidence in the literature indicating that organizational capacity is influencing corporate performance,this study further examines the influence of corporate governance by combining it with organizational capacity. This study employs mail questionnaire in assessing the performance of companies. Using the data from the mail questionnaire, no significant relationship was found between independent director, CEO duality, board size, ownership concentration, financial management and corporate performance. Additionally, findings from the mail questionnaire showed that organizational learning was significant in explaining corporate performance. Two contributions are acknowledged in this research. First, the application of a mail questionnaire extends the research methodology on corporate performance and adds value in respect of how findings from the questionnaires highlight the perceptions of individuals pertaining to the research objectives. Second, using organizational capacity as an explanatory factor, this study documents that organizational learning emerges as an important aspect in influencing the performance of Malaysian companies.